Analisis Pengaruh Variasi Beban Terhadap Kinerja Turbin Pelton - Selasiah, Selasiah; Kismanti, Shinta Tri; Sudirman, Sudirman (Universitas Borneo Tarakan, 2025)
The research focused on the effect of lamp variations on the performance of Pelton turbines which include power, torque, generator rotation and turbine rotation, as well as the resulting efficiency. The research used an experimental method that involves the testing of load variations using LED lights with wattages of 3 watt, 5 watt, and 7 watt. The results of the research were presented in the form of graphs, then compared so that the effect of workload variations on Pelton turbines. The tests were conducted and the results showed that the highest turbine rotation of 1917.1 rpm achieved at a load of 7 watts, while the lowest rotation of 1156.9 rpm at a load of 3 watts. While the generator rotation shows the highest rotation of 1858.8 rpm at a load of 7 watts and the lowest 1222 rpm at a load of 3 watts. The generator electrical power reached the highest value of 0.314 watts at 5 watts load, while the highest efficiency of 10.29% was also achieved at 5 watts load. Thus, the greater the workload given, the higher the rotation produced, the voltage decreases, and the greater the power required.